2019
DOI: 10.1038/s41598-019-40213-5
|View full text |Cite
|
Sign up to set email alerts
|

Surveying of acid-tolerant thermophilic lignocellulolytic fungi in Vietnam reveals surprisingly high genetic diversity

Abstract: Thermophilic fungi can represent a rich source of industrially relevant enzymes. Here, 105 fungal strains capable of growing at 50 °C and pH 2.0 were isolated from compost and decaying plant matter. Maximum growth temperatures of the strains were in the range 50 °C to 60 °C. Sequencing of the internal transcribed spacer (ITS) regions indicated that 78 fungi belonged to 12 species of Ascomycota and 3 species of Zygomycota, while no fungus of Basidiomycota was detected. The remaining 27 strains could not be reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
7
24
0
Order By: Relevance
“…Poor growth on Avicel could result from lack of cellulase induction or the elevated crystallinity of Avicel. Growth discrepancies between the two T. terrestris strains LPH172 and CBS 117535 corroborate previously reported differences in biomass degradation and enzyme production between strains of the same species (16). Recently, de Vries and Mäkelä reported that related fungi with similar genomic content produced highly diverse sets of enzymes, even when grown on the same plant biomass substrates.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Poor growth on Avicel could result from lack of cellulase induction or the elevated crystallinity of Avicel. Growth discrepancies between the two T. terrestris strains LPH172 and CBS 117535 corroborate previously reported differences in biomass degradation and enzyme production between strains of the same species (16). Recently, de Vries and Mäkelä reported that related fungi with similar genomic content produced highly diverse sets of enzymes, even when grown on the same plant biomass substrates.…”
Section: Discussionsupporting
confidence: 86%
“…Isolation and maintenance of fungi Samples containing decaying plant residues (compost, grasses, rice straw, mushroom ground, wood, and soil) were collected from different provinces in Northern Vietnam during 2012-2016. Fungal strains were isolated as described by Thanh et al (16) by incubation at 50 °C and under acidic conditions (pH 2.0) on medium containing untreated rice straw as the sole carbon source. After 7-10 days of incubation, fungal colonies were transferred to potato dextrose agar (PDA) plates and puri ed by hyphal tip culture at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations